2015
DOI: 10.1186/s13064-015-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of RBM8a in proliferation and differentiation of embryonic neural progenitors

Abstract: BackgroundNonsense mediated mRNA decay (NMD) is an RNA surveillance mechanism that controls RNA stability and ensures the speedy degradation of erroneous and unnecessary transcripts. This mechanism depends on several core factors in the exon junction complex (EJC), eIF4A3, RBM8a, Magoh, and BTZ, as well as peripheral factors to distinguish premature stop codons (PTCs) from normal stop codons in transcripts. Recently, emerging evidence has indicated that NMD factors are associated with neurodevelopmental disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 90 publications
2
46
1
Order By: Relevance
“…Although both studies are concordant regarding outcomes of Rbm8a loss of function, there is some discrepancy in overexpression phenotypes. While our group did not observe overexpression phenotypes in the developing cortex, Zou et al (2015) report reduced cell cycle exit and less neuron production upon overexpression. These differences could be due to the timing of the experiment, nature of overexpression, or brain region in which overexpression was examined.…”
Section: Roles Of the Ejc In Embryonic Neurogenesiscontrasting
confidence: 70%
See 1 more Smart Citation
“…Although both studies are concordant regarding outcomes of Rbm8a loss of function, there is some discrepancy in overexpression phenotypes. While our group did not observe overexpression phenotypes in the developing cortex, Zou et al (2015) report reduced cell cycle exit and less neuron production upon overexpression. These differences could be due to the timing of the experiment, nature of overexpression, or brain region in which overexpression was examined.…”
Section: Roles Of the Ejc In Embryonic Neurogenesiscontrasting
confidence: 70%
“…Upon completion of neurogenesis, Emx1‐ Cre; Rbm8a lox/+ mice displayed disorganized cortical layers, with preferential loss of upper layer neurons. Some of these results were independently corroborated by another group, who used shRNA knockdown of Rbm8a in neural progenitor culture (Zou et al, 2015). Consistent with our study, the authors find Rbm8a knockdown increases cell cycle exit and neuron production.…”
Section: Roles Of the Ejc In Embryonic Neurogenesismentioning
confidence: 67%
“…Therefore, the observation of the HYDIN paralog expressed in humans may be a candidate gene for microcephaly, since it is only expressed in the brain and is important in head size determination [Brunetti-Pierri et al, 2008;Olbrich et al, 2012]. Recently, it was shown that the RBM8A gene within the 1q21.1 region, besides its role in the thrombocytopenia-absent radius syndrome genesis, also disrupts the embryonic cortical development resulting in neurodevelopmental phenotypes associated to microcephaly [Mao et al, 2015;Zou et al, 2015].…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps not surprisingly, most of the SCZ-related genes seen within the CNVs identified have also been associated with other neuropsychiatric and neurodevelopmental conditions, contributing further evidence to support the neurodevelopmental continuum model (Davis et al, 2016; Owen and O’Donovan, 2017). For example, the RMB8A gene contained within the 1q21.1 microdeletion in patient 15 has been associated with ID and anxiety behaviours (Alachkar et al, 2013; Gamba et al, 2016; Zou et al, 2015), while deletions of NRXN1 , seen in two patients, are strongly associated with neuropsychiatric and neurodevelopmental disorders, including SCZ and ASD (Kirov et al, 2009; Marshall et al, 2017; Rujescu et al, 2008). Deletion of LMAN2L , a gene associated with increased risk for SCZ, bipolar disorder and ID (Lim et al, 2014; Rafiullah et al, 2016), was found in three patients.…”
Section: Discussionmentioning
confidence: 99%